Telaah Keberagamaan Menyingkap Peran Forum Kerukunan Umat Beragama (FKUB) di Kabupaten Pamekasan - Baitur Rohman; Syaiful Azmi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
Interfaith harmony is a crucial aspect in maintaining social stability in a pluralistic society, both in terms of differences in faith and denomination. This study aims to examine the role of the Pamekasan Regency Interfaith Harmony Forum (FKUB) in maintaining interfaith harmony and to identify factors that hinder its performance. The method used was a qualitative approach through interviews, observation, and documentation of relevant parties. The results of the study indicate that the role of the Pamekasan FKUB in maintaining interfaith harmony has not been optimal. The FKUB is considered slow in responding to conflicts and only acts after the issue has become public attention, so some people choose to resolve conflicts independently. In some cases, conflict resolution is also considered to violate the rights and obligations of members of other religions. The obstacles affecting the FKUB's performance consist of internal factors, such as minimal attention and support from the local government in terms of funding and facilities; and external factors, namely the community's low understanding of interfaith tolerance, which leads to fanaticism and vulnerability to provocation. Therefore, it is necessary to strengthen the capacity of the FKUB and increase tolerance literacy in the community.